Controlled therapeutic trial of levamisole and sulphasalazine in acute ulcerative colitis. Issue 5 (May 1984) - Hermanowicz, A; Nowak, A; Gajos, L
Abstract : Forty five patients with acute ulcerative colitis were randomly allocated to receive (a) sulphasalazine, (b) levamisole, or (c) a combination of sulphasalazine and levamisole. Each group contained 15 patients. The ulcerative colitis activity index (UCAI), the remission and relapse rates were compared at three monthly intervals for one year. The UCAI fell in each group. Detailed analysis of all clinical and biochemical parameters used for estimation of UCAI showed that the only difference was in patients receiving combined therapy who continued to have a raised ESR and platelet count. Fewer patients, however, went into remission on levamisole therapy (46.6%) compared with the other two groups (66.6%). The cumulative relapse rate was 20% for those receiving levamisole compared with 6.6% in the other groups. Side effects were observed in 20% of patients receiving levamisole, 26% receiving sulphasalazine, and 40% in those having combined therapy. The results indicate that levamisole is unlikely to have a major role in the management of patients with ulcerative colitis.